2016
DOI: 10.1016/j.jdent.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial on arresting dental root caries through silver diammine fluoride applications in community-dwelling elders

Abstract: In a water fluoridated area, annual application of SDF solution or SDF/KI solution can arrest dental root caries in elders. In the long term, application of KI does not reduce the blackening of arrested caries lesions caused by SDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
121
0
19

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(150 citation statements)
references
References 21 publications
4
121
0
19
Order By: Relevance
“…Silver ions in the SDF solution can blacken the tooth structure. It is suggested that the KI solution can react with SDF to form a bright yellow solid compound (silver iodide) [30], and this reaction could reduce the excess free silver ions which result in the black staining [27]. Although the bright yellow precipitates can be seen after the application of KI, the staining of tooth surfaces could still be detected in SDF + KI treatment group in this study.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Silver ions in the SDF solution can blacken the tooth structure. It is suggested that the KI solution can react with SDF to form a bright yellow solid compound (silver iodide) [30], and this reaction could reduce the excess free silver ions which result in the black staining [27]. Although the bright yellow precipitates can be seen after the application of KI, the staining of tooth surfaces could still be detected in SDF + KI treatment group in this study.…”
Section: Discussionmentioning
confidence: 65%
“…In this study, SDF + KI treatment led to discolouration of tooth surfaces although the intensity of the discolouration was less than that of SDF treatment. One possible explanation may be that the amount of the applied KI solution was not sufficient to lead to an excess of free silver ions remaining [30]. Besides, silver iodide is considered to be highly photosensitive which can dissociate into metallic silver and iodine by exposure to light.…”
Section: Discussionmentioning
confidence: 99%
“…Some commercial products with both products are available (Riva Star, SDI, Baywater, Victoria, Australia). However, one of the trials for adults 58 reported that potassium iodide application had no effect in reducing the black stain on root caries, especially in the long term.…”
Section: Current Evidence On the Efficacy Of Silver Diamine Fluoride mentioning
confidence: 99%
“…This material has the added advantage of only requiring a single professional application annually, and thus reduces the burden of care in vulnerable dependent patients. In a randomised clinical trial with a 30‐month observation period, Li et al demonstrated that approximately 90% of active root carious lesions were arrested with an annual application of SDF varnish …”
Section: Prevention Strategies In Older Adultsmentioning
confidence: 99%